(untitled) (Interdisciplinary Studies Journal, 2025)
The study was conducted with nine students with disabilities from a public university in Pará. The objective is to analyze the relationship between students with disabilities and their teachers, aiming to identify the importance of attitudinal accessibility. The survey results were organized into two categories: attitudinal and interpersonal. The attitudinal category highlights reports of teacher behaviors that either facilitated or hindered the learning and participation of students with disabilities. The interpersonal category presents reports of relationship-building between students and teachers, describing either positive relationships and their effects or conflicts experienced. The study suggests that attitudinal accessibility is fundamental to the inclusion of students with disabilities in higher education. Adapting educational materials, fostering healthy relationships, and appropriately resolving conflicts are essential to ensuring the full participation and learning of students with disabilities.